Steamboat BELLA departing from Dawson with eight tons of gold, Yukon Territory, 1898. - Hegg, Eric A., 1867-1948 (1898)
Also shows the steamboat ORA and a large scow at the boat landing. Caption on image: ""Bella" departing from Dawson City with eight tons of gold. 1898" Original image in Hegg Album 9, page 43.